2004 IEEE International Conference on Communications (IEEE Cat. No.04CH37577) 2004
DOI: 10.1109/icc.2004.1313200
|View full text |Cite
|
Sign up to set email alerts
|

A robust 60 GHz wireless network with parallel relaying

Abstract: The challenge at millimeter-wave frequencies is that the propagation characteristics approximates to that of light. In a non line-of-sight scenario, when even the mobile station (MS) is near the base station, the attenuation may be tens of dBs due to shadowing and obstructions. Increasing the number of base stations reduces such effects but at the expense of cost and complexity. An attractive method to mitigate such shadowing effects is to use dedicated active or passive relay stations. Proposed here is a netw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(9 citation statements)
references
References 5 publications
0
9
0
Order By: Relevance
“…In addition to incorporating modules of directional antennas, a challenge is the cross layer modelling issue that involves embedding an accurate physical layer model of 60 GHz channels. To this end, some of the previous work on 60 GHz PHY conducted at our laboratory may be leveraged [5]. To gain insights into realistic application performance of 60 GHz systems, study of transmitting uncompressed HDTV video over 60 GHz networks is also part of our future work.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to incorporating modules of directional antennas, a challenge is the cross layer modelling issue that involves embedding an accurate physical layer model of 60 GHz channels. To this end, some of the previous work on 60 GHz PHY conducted at our laboratory may be leveraged [5]. To gain insights into realistic application performance of 60 GHz systems, study of transmitting uncompressed HDTV video over 60 GHz networks is also part of our future work.…”
Section: Discussionmentioning
confidence: 99%
“…As mentioned previously, in 60 GHz systems an obstacle in the LOS path between the transmitter and receiver can attenuate the signal by 20-30 dB [5], resulting in link outage. In other words, the one-hop link between two nodes can be easily blocked or broken by obstacles.…”
Section: Multi-hop Networking a Signal Quality Based Routingmentioning
confidence: 94%
“…Herein, we investigate the performance of such deployment considering the use of mmWave communication. Hence, the blockage effects on the mmWave signal should be taken into account in the investigation, as the works in [9]- [11] have shown that the link performance from a single ceiling-mounted mmWave transmitter can be degraded by human body blockage.…”
Section: Related Workmentioning
confidence: 99%
“…Such architectures require additional costs and have overhead in terms of complexity and interference. Other than increasing the number of deployed access units, using dedicated relay stations is another method [5], [6]. In this scheme, relay stations are used to relay packets when there is no line-of-sight between the source and the destination units.…”
Section: Introductionmentioning
confidence: 99%